A utilização da mediação de conflitos pelo comitê de bacia hidrográfica do Rio Sergipe como instrumento de efetivação da gestão descentralizada dos recursos hídricos - Araújo, Vanessa Gomes de (2020)
Parallel to the growing demand for multiple uses of water, conflicts arise among its users, contributing to the increase in the number of cases submitted to the Judiciary. In this sense, this study aims to analyze the existence of mediation as a method of resolving possible conflicts related to water resources in the Sergipe River Hydrographic Basin. The research with a qualitative approach was developed based on a bibliographic survey, through consultations with books, legislation relevant to the theme, articles in scientific and non scientific journals and, documentary, through the analysis of the minutes of the Sergipe River Basin Committee meetings, its Internal Regulations and the Climatological Report that analyzes the variability of rainfall by regions in Sergipe, from 2000 to 2017. The results show that despite advancing towards recognizing mediation as a method of conflict resolution, the Committee faces several difficulties in realization of decentralized management of water resources, especially with regard to the resolution of water disputes. Possible solutions to some of the problems faced by the Committee can be identified, such as the training of its members in the management of water resources and conflict management, in addition to making them aware of frequent participation in Committee meetings and also encouraging the participation of the population in these meetings.